Prevalence and Determinants of Fluor Albus Among Postmenopausal Women Without Symptoms: Implications for Public Health Screening Programs - Purnamasari, Yenti; Hamid, Firdaus; Saimin, Juminten; Bukhari, Agussalim (Public Health of Indonesia, 2025)
Background: Postmenopausal women are susceptible to vaginal infections due to hormonal changes that alter the vaginal microbiota, potentially leading to fluor albus even in the absence of symptoms. Objective: This study aims to determine the prevalence of Fluor Albus and assess its relationship with age, age of menopause, and duration of menopause in postmenopausal women. Methods: A cross-sectional study was conducted from April to July 2024 at Kendari City, Southeast Sulawesi, Indonesia. A total of 35 postmenopausal women were selected through total sampling, excluding those with chronic illnesses, vaginal symptoms, recent antibiotic use, or vaginal cleansing. Data were collected through participant-completed forms and laboratory examinations using KOH smear and Gram staining to detect the presence of Candida and pathogen bacteria. Data were analyzed using descriptive statistics and Chi-square tests. Results: The prevalence of fluor albus in postmenopausal women in this study was 68.6%. There was no statistically significant relationship between age (0.628), age of menopause (0.150), or duration of menopause (0.269) with the incidence of fluor albus. Conclusion: The prevalence of fluor albus among postmenopausal women in this study was high and was not related with age, menopausal age and duration of menopause, underlining the importance of regular reproductive health screening in the postmenopausal group.